Challenges arising from the use of TiO2/rGO/Pt photocatalysts to produce hydrogen from crude glycerol compared to synthetic glycerol - Ribao, Paula (2020)
ABSTRACT: Photoreforming has emerged as a novel technology expected to obtain chemical energy through solar energy transformation. In this way, sustainable valorization of glycerol, a biodiesel by-product, to clean fuels is a promising alternative to help meet the world's growing energy demand. In this work, TiO2/rGO(x)/Pt(y) photocatalysts have been developed for hydrogen production from synthetic and crude glycerol solutions. The effect of several key operating parameters (including vol% of glycerol, pH, catalyst loading, wt% of GO, wt% of Pt, temperature, and light source) on hydrogen production rate has been studied. The results indicated different optimal operating parameters depending on glycerol origin, achieving up to 70.8 and 12.7 mmol h(-1) g(-1) of hydrogen using synthetic glycerol and crude glycerol, respectively. Additionally, GO nanosheets and Pt nanoparticles strongly influenced the hydrogen production rate but not the overall reaction mechanism. Impurities contented in crude glycerol are key factors in developing realistic hydrogen production processes.